Analysis of Understanding Chemical Bond Concepts in Students with Three-Tier Multiple Choice - Mellyzar Mellyzar (Journal of Educational Chemistry (JEC), 2021)
One type of diagnostic test is a three-tier multiple choice, which is a test question in the form of choices consisting of three questions, the first part is about the concept of the topic, the second part is the reason refers to the first question, and the third part is the level of confidence in the two previous questions. Students' understanding of chemical bonding. The method used is descriptive with the research subject of 93 students of chemistry education. Data collection with 14 three-tier multiple choice test questions and analysis of students' level of understanding using the Certainty of Responses Index (CRI) technique. The results showed that the understanding of the concept of chemical bonds was very low at 29.50% and misconceptions at 62.77% in the high category. With high student misconceptions, it means that the concept of chemical bonds that they have is still not in accordance with the truth. Based on these findings, for teachers there needs to be special preparations and strategies to improve students' understanding of concepts, for example carrying out learning using methods that are in accordance with the characteristics of the material presented or by using appropriate learning media.